Pengembangan Media Interaktif Kit Berhitung Berbasis Arduino Uno Untuk Meningkatkan Hasil Belajar Siswa - Destira Destira; Yuli Witanto (Educatio, 2026)
The low learning outcomes of students in mixed arithmetic operations are caused by difficulties in understanding the concepts and sequence of arithmetic operations and the limited use of interactive learning media. Therefore, an interactive learning media in the form of an Arduino Uno-based counting kit was developed as an alternative solution for mathematics learning in elementary schools. This study aims to develop an interactive learning media for the counting kit and test its feasibility and effectiveness in improving the learning outcomes of fifth-grade students at SD Negeri 02 Karanggeneng, Grobogan Regency. The method used by the researcher is Research and Development (R&D) with the ADDIE development model consisting of the stages of analysis, design, development, implementation, and evaluation. The research subjects were 28 fifth-grade students with a saturated sampling technique. Data collection techniques include observation, interviews, questionnaires, and tests, while data analysis was carried out qualitatively and quantitatively through a feasibility test, paired sample t-test, and N-Gain test. The results of the study indicate that the interactive learning media for the Arduino Uno-based counting kit was declared feasible by material experts and media experts. In addition, the use of this media has proven effective in improving student learning outcomes, as indicated by a significant difference between pretest and posttest scores and an increase in the N-Gain score in the moderate category. Thus, the Arduino Uno-based interactive counting kit learning media is feasible and effective for use in mathematics learning on mixed arithmetic operations in elementary schools.